The Old, the New and the Unknown – Russia, China and India in the Race for the Arctic - Breiteneicher, Felix; Garlick, Jeremy; Shakhanova, Gaziza; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2021)
The Arctic has experienced a geographical and geopolitical opening over the last decades, involving more and more players in political, commercial and military Arctic affairs. This work qualitatively compares the policies of Russia, China and India in the region and critically assesses the geostrategic potential for both cooperation and conflict between them. Russia has the biggest share and impact in the Arctic and is sticking to the institutional rules of the game, but it fears that its national sovereignty and resource riches are threatened by external actors. At the same time, Moscow is largely dependent on foreign investment to develop its northernmost territories, inter alia, from China and India. China has built up a considerable commercial and scientific ‘stakeholder’ presence in the region, but its unconventional approaches have evoked fears. Beijing is nevertheless more interested in keeping the regional governance stable and making friends rather than foes, especially concerning Russia. India still has to consolidate its Arctic strategy, focusing on environmental sustainability. New Delhi’s stance towards the High North is characterised by both its rivalry with China as well as a dichotomy between hard and soft power, visible in Russia.
Vedoucí práce: Jeremy Alan Garlick
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2021
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2021
Způsob přístupu: Internet
Keywords: international and diplomatic studies [obor dipl. práce]; diplomové práce; master's theses